2014
DOI: 10.1007/s11904-014-0235-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Benefits of Antiretroviral Therapy in Vietnam: Towards Ending AIDS

Abstract: Vietnam has a concentrated HIV epidemic, with the highest HIV prevalence being observed among people who inject drugs (PWID). Based on its experience scaling-up robust HIV interventions, Vietnam aims to further strengthen its response by harnessing the preventive benefits of antiretroviral therapy (ART). Mathematical modelling suggests that prioritizing key populations for earlier access to ART, combined with other prevention interventions, may have significant impact on the epidemic, cost-effectively reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…This finding is consistent with a high prevalence of late presentation to care in Vietnam [33]. Despite expanding access to ART in the country, the median CD4 cell count at ART initiation was 197 cells/mm 3 in 2013 [23,34]. In our study, 68% presented with CD4 <250 cells/mm 3 and 35% with clinical stage IV.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with a high prevalence of late presentation to care in Vietnam [33]. Despite expanding access to ART in the country, the median CD4 cell count at ART initiation was 197 cells/mm 3 in 2013 [23,34]. In our study, 68% presented with CD4 <250 cells/mm 3 and 35% with clinical stage IV.…”
Section: Discussionsupporting
confidence: 88%
“…In a cohort of Swedish and Danish PLWH[70], PWID were less likely to be “successfully managed” (viral suppression among those eligible for ART or at least annual CD4 testing among those ineligible) than MSM or heterosexuals (78% among PWID vs 92%). PWID initiate care later than those who do not inject drugs, as found by a study in Vietnam where PWID started ART at 69 CD4+ cells/mm 3 compared to 96 CD4+ cells/mm 3 among non-injectors[71]. Another study found PWID in Belgium diagnosed in 2007–2010 were less likely to be retained in HIV care compared to heterosexuals[72].…”
Section: Cascade Outcomes In Key Populationsmentioning
confidence: 99%
“…Recent studies have found that OST among PWID is associated with higher CD4+ cell count at ART initiation[71], ART initiation and access[83,84], ART medication adherence[85,86], decreases in ART discontinuation[87], and decreases in delayed care visits[88]. …”
Section: Recent Work In Interventions To Improve Outcomes For Key Popmentioning
confidence: 99%
“…For PWID in Vietnam, low levels of education may serve as a barrier for HIV and substance use treatment . We believe the limited number of females in Indonesia and Vietnam accurately reflects the population of PWID in these countries based on culture and historic precedence . The gender distribution in Ukraine is similar to the distribution in Russia and the Baltic States .…”
Section: Discussionmentioning
confidence: 85%